2016
DOI: 10.1016/j.expneurol.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of functional properties of hippocampal networks following repetitive closed-head injury

Abstract: Traumatic brain injury (TBI) is the leading cause of death for persons under the age of 45. Military service members who have served on multiple combat deployments and contact-sport athletes are at particular risk of sustaining repetitive TBI (rTBI). Cognitive and behavioral deficits resulting from rTBI are well documented. Optimal associative LTP, occurring in the CA1 hippocampal Schaffer collateral pathway, is required for both memory formation and retrieval. Surprisingly, ipsilateral Schaffer collateral CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 113 publications
4
23
0
Order By: Relevance
“…Injury of visual cortex is followed by processes of enhanced neuroplasticity like LTP49. Other studies found an increase in LTP was observed after closed head injury in hippocampal CA150. These data support the view that that a compensatory mechanism for LTP or a mechanism of remodeling the neuronal networks is plausible following injury.…”
Section: Discussionsupporting
confidence: 74%
“…Injury of visual cortex is followed by processes of enhanced neuroplasticity like LTP49. Other studies found an increase in LTP was observed after closed head injury in hippocampal CA150. These data support the view that that a compensatory mechanism for LTP or a mechanism of remodeling the neuronal networks is plausible following injury.…”
Section: Discussionsupporting
confidence: 74%
“…While the long-term effects of glutamate-induced excitotoxicity generally involve epileptic seizures, disruption of long-term potentiation and depression, dysregulated sEPSCs, and miniature EPSCs 48, 50, 59 , the acute effects of injury on neuronal electrophysiology are poorly characterized. In this study, we demonstrated that NMDA-induced sublethal damage causes a significant decrease in both frequency and amplitude of sEPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, brain injury is associated with enhanced fear acquisition (Reger et al, 2012;Schneider et al, 2016), impaired fear extinction (Schneider et al, 2016), and altered fear circuitry (Palmer, Metheny, Elkind, & Cohen, 2016) (but see (Sierra-Mercado et al, 2015)). However, specific effects appear to depend on methods used to model brain injury (Genovese et al, 2013;Logue, Cramer, Xu, Perl, & Galdzicki, 2015;Palmer et al, 2016) and it is unclear how accurately animal models reflect TBI in humans. Improved understanding of the effects of TBI on fear learning may facilitate treatment and prevention efforts for individuals recovering from head injury.…”
Section: Introductionmentioning
confidence: 99%